International financial reporting standards and financial information quality: principles versus rules-based standards - Seyed Sajad Ebrahimi Rad,; Zaini Embong, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The objective of the present study is to examine whether the adoption of International Financial Reporting Standards (IFRS) increases financial information quality. The IFRS brings about substantial changes in accounting standards. One of the prominent features of the system is that it results in the production of financial information of higher quality. Most extant studies in this area are performed at firm-level. The present study, on the other hand, examines the impact of IFRS adoption at the country-level. Environmental determinism theory states that accounting is a function of environmental variables, such as ownership structure, information environment and capital market condition. Therefore, the impact of IFRS adoption could be different across different countries. The present study addresses the existing lack of research that compares the outcomes of IFRS adoption between countries. Besides comparing the quality of financial information before and after the adoption of IFRS, the present study also compares the effects of IFRS adoption between countries with different accounting bases prior to the adoption. The results show that financial information quality, measured by five indicators, improves after IFRS adoption; and that the impact is more prevalent in a rules-based country compared to a principles-based country.